Filmes poliméricos a base de carboximetil celulose reforçados com nanocelulose com potencial para encapsular o agente de biocontrole Trichoderma harzianum - Ferreira, Aline Medeiro (Universidade Federal de São Carlos, 2024)
The use of microorganisms for pest and disease biocontrol in plants represents an environmentally friendlier alternative to agrochemicals, potentially contributing to the development of more sustainable agriculture. Among the microorganisms marketed as biopesticides, the fungus Trichoderma harzianum (T. harzianum) stands out due to its various mechanisms of action against pathogens. However, the viability of microbial inoculants still needs to be improved to ensure better field efficiency and longer shelf life. In this regard, formulations for microbial encapsulation have emerged as a promising strategy to enhance the properties of these bioproducts. Among the polymers with potential for microbial encapsulation, carboxymethyl cellulose (CMC) stands out due to its origin derived from cellulose, the most abundant natural polymer in nature. However, considering its mechanical limitations, the incorporation of cellulose nanocrystals (CNC) as reinforcing agents has been studied. Thus, the present study aimed to develop polymeric matrices based on low and medium viscosity CMC reinforced with CNC for the encapsulation of T. harzianum aiming at application as a coating for fertilizer granules. The films were produced by the casting method, characterized regarding their physicochemical and morphological properties, before and after the addition of the microorganism. In addition, assays were performed with the encapsulated microorganism for plate growth, spore release in saline solution, and viability during a 3-month storage period. The results obtained indicate that matrices based on 1.5% carboxymethyl cellulose (medium viscosity) (CMCmedium) and the nanocomposite with 1.5% CMCmedium and 0.25% CNC showed better results in terms of surface uniformity, mechanical resistance, slower solubility profiles in water, lower degree of swelling, slower release of the microorganism from the matrix, and viability over time. The use of these matrices in coating MAP fertilizer granules did not interfere with the growth of T. harzianum. These results highlight the efficiency of the proposed formulations as a potential strategy for coating fertilizer granules and delivering microorganisms.
Polymeric films based on carboxymethyl cellulose reinforced with nanocellulose with potential to encapsulate the biocontrol agent trichoderma harzianum
Keywords: Inoculante microbiano; Biocontrole; Encapsulamento; Trichoderma harzianum; Nanocelulose; Carboximetil celulose; Microbial inoculant; Encapsulation; Biocontrol; Nanocellulose; Carboxymethyl cellulose; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA